Ending hunger, malnutrition, and poverty - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
The combination of IFPRI’s cutting-edge research and Japan’s advanced technologies and know-how enable our work with Japan to not only address the current emergencies but also build resilience to future crises and support sustainable development. Throughout its work, IFPRI conducts rigorous evaluations, using innovative methods such as randomized controlled trials (RCT), to measure the impact of interventions and develop clear evidence to inform policymaking.